RANCANG BANGUN SISTEM INFORMASI KAS RT 4 RW 01 KAVLING NATO KEL. SUNGAI LANGKAI KEC. SAGULUNG BERBASIS CODEIGNITER - Effendi, Bagus Cecep; Elisa, Erlin (LPPM Universitas Putera Batam, 2021)
Research design related to website-based applications for recording RT and RW cash where this application aims to facilitate the process of recording population data, recording RT cash, submitting cover letters and transparency of incoming and outgoing cash, so that residents can find out the cash budget. This program uses UML (Unified modeling language) for the process of describing the design of this program using SDLC (System development life cycle).